An evaluation of the utilization of self-help materials in the UP Social Science Library section - Borres, Randy G.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study on the evaluation of the utilization of self-help materials in the UP Social Science Library Section aimed to determine what self-help materials in the Social Science section are used by students and to identify the type of self-help materials needed by the Social Science Library section users. Also, the study brought emphasis on the purposes of the students in using self-help materials and their individual topic preferences. The Social Science Library section users from February 22 - March 1 of the 2nd semester AY 2009-2010 were the respondents of the study. One-hundred forty respondents answered the survey and 207 books in the Social Science Reading Room and Social Science Stacks Section were examined. Most of the respondents came from the College of Social Science and Philosophy (CSSP). Majority of the respondents visit the library everyday and once or twice a month and the average hours of visit is 4.26 hours per week.
Based on the results of the study, respondents were aware of self-help materials but only a few are actually using them. There were respondents who were both not aware and have not used any self-help material. The materials were used for academic purposes as there are different academic requirements considered for using self-help materials like research papers, reports, assignments, and quizzes. Also, the materials were used for non-academic purposes like practical, personal, hobbies, and some stated that they use it for past time and "do-it-yourself repairs".
Majority of the respondents who use self-help materials prefer using other formats specifically online sources because of their unavailability and bulkiness. Most of the self-help users prefer the topic under psychology, history, and sociology. The availability of self-help materials in the Social Science Library Section were rated as moderate to high and showed a good availability rating when it comes to the collection of the library. Most of the respondents were willing to learn more about the usefulness of self-help materials and only a few were not interested. The study showed that at least at the age of 18-19 many respondents were aware and have used self-help materials and are appreciative of its existence and advantages. Majority of the books are located in the Reading Room section and older books in the Social Science Stack Room. Also, results showed that there are some missing books in the collection. Books were borrowed 813 times from the year 2000-2010 and majority of these books were under the topic of psychology.
The researcher recommended that there should be added acquisitions of self-help materials especially on those topics that have a high demand such as Psychology and Sociology. A study could be made regarding the evaluation and collection development of the self-help materials collection in the Social Science Library section focusing more on the user's demand, acquisition and collection expansion. Also, another study could be made focusing on a more qualitative approach on the usefulness of self-help materials and the availability of self-help in all other formats and how to take advantage of them.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) College of Social Science and Philosophy Library; Library materials -- Philippines -- Quezon City